Social robotics : 6th International Conference, ICSR 2014, Sydney, NSW, Australia, October 27-29, 2014. Proceedings - Johnston, Benjamin; Williams, Mary-Anne; Beetz, Michael (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 6th International Conference on Social Robotics, ICSR 2014, held in Sydney, NSW, Australia, in October 2014. The 41 revised full papers presented in this book were carefully reviewed and selected from numerous submissions. Amongst others, topics covered are such as interaction and collaboration among robots, humans, and environments; robots to assist the elderly and persons with disabilities; socially assistive robots to improve quality of life; affective and cognitive sciences for socially interactive robots; personal robots for the home; social acceptance and impact in the society; robot ethics in human society and legal implications; context awareness, expectation, and intention understanding; control architectures for social robotics; socially appealing design methodologies; safety in robots working in human spaces; human augmentation, rehabilitation, and medical robots; robot applications in education, entertainment, and gaming; knowledge representation and reasoning frameworks for robot social intelligence; cognitive architectures that support social intelligence for robots; robots in the workplace; human-robot interaction; creative and entertaining robots.